Collaborative Governance In Flood Mitigation In Bojonegoro Regency - Widyarta, Agus; Hidayat, Endik; Kriswibowo, Arimurti (CV. Inara, 2022)
The involvement of the government, community, and private sector is required in flood mitigation in Bojonegoro Regency. The problem is how to initiate and run the optimal collaborative efforts with these stakeholders. This study was conducted with a qualitative approach and data collection through interviews with key informants of state actors. The study found that less efficient flood mitigation in Bojonegoro was because the elements of the state and civil society remained working individually under their duties and responsibilities rather than in integrated processes. This proves the less effective collaborative government Disaster Management in Bojonegoro.